Spiroraslaser: an interactive visual art system using hybrid raster–laser projection. (1st January 2011) - Halabi, Osama; Motomura, Kenta; Chiba, Norishige
This paper explores the possibility of generating visual imagery in a highly interactive environment on the basis of hand position and acceleration. We present a new display method called hybrid raster–laser projection for combining two projections to create a final visual image. A Wii Remote Controller tracks hand orientation, acceleration and movement, and the graphics are generated by using hypotrochoids. The raster and the laser images are carefully synchronised in order to ensure homogenously integrated visuals. The resultant images are unique and beautiful because of the higher degree of contrast of the laser projection compared to the raster projection. This contrast creates lively, floating images that can be achieved only by using the proposed system. The proposed system presents a new interactive approach to the realtime creation of visual art and a novel method for displaying these visuals.